The influence of community-acquired pneumonia on the clinical course of coronary heart disease: the results of retrospective analysis - Mykhailovska, Natalia; Kulynych, Tamila (ScienceRise: Medical Science, 2017)
The aim of the work: To investigate the effect of the community-acquired pneumonia (CAP) on the clinical course of coronary heart disease (CHD) and the frequency of major cardiovascular events incidence based on the retrospective analysis results. Methods: The retrospective analysis of 203 case histories of patients with CHD (median age 73 years (63.00, 80.50), score on the PSI/PORT – 80 (69; 93)), hospitalized in the therapeutic department because of CAP was performed. The study of the main cardiovascular events was conducted with each patient or his relatives through telephone conversations. The data on readmission and reference of the patient to medical institutions in the consequence of arrhythmic complications, progression of heart failure, destabilization of coronary artery disease within 1 year after the transmitted pneumonia were considered. By cumulative endpoint attributed all fatal and nonfatal cardiovascular events that occurred during the year after CAP. Results: In total, in patients with CHD during 1 year after the transferred CAP was recorded 104 cardiovascular events, 37 (18.23 %) patients needed the re-hospitalization. The most common causes of health aggravation in patients with CHD after CAP were the rhythm and conduction abnormalities, the occurrence or decompensation of pre-existing heart failure and deterioration of angina pectoris. Among the hospitalized patients, 20 (62.5 %) had a combination of 2 or more of the noted complications. The development of acute myocardial infarction was observed in 3 (1.48 %) patients at 7 and 9 days from the moment of admission for hospitalization. The arrhythmias, acute myocardial infarction and decompensation of heart failure were observed with the same frequency in patients of all groups, regardless of the severity of pneumonia and the risk of mortality on the PSI/PORT scale. There were not found the impact on the development of adverse cardiovascular events in patients with CHD after CAP such factors as male gender, presence of anamnesis of transmitted myocardial infarction, arterial hypertension, angina pectoris III-IV FK, previous arrhythmic disorders, and also such traditional factors as smoking and diabetes mellitus. Conclusions: The community-acquired pneumonia exerts an adverse effect on the clinical course of coronary heart disease by increasing the functional class of angina, heart failure progress and the development of arrhythmic; the most common cause of the lethal outcome in patients with coronary heart disease after community-acquired pneumonia is acute heart failure (alveolar pulmonary edema).There was not found the relationship between traditional risk factors, severity of CAP and the development of adverse cardiovascular events